Structure of S. pombe telomerase protein Pof8 C-terminal domain is an xRRM conserved among LARP7 proteins. Issue 8 (3rd August 2021) - Basu, Ritwika; Eichhorn, Catherine D.; Cheng, Ryan; Peterson, Robert D.; Feigon, Juli
ABSTRACT: La-related proteins 7 (LARP7) are a class of RNA chaperones that bind the 3′ ends of RNA and are constitutively associated with their specific target RNAs. In metazoa, Larp7 binds to the long non-coding 7SK RNA as a core component of the 7SK RNP, a major regulator of eukaryotic transcription. In the ciliate Tetrahymena the LARP7 protein p65 is a component of telomerase, an essential ribonucleoprotein complex that maintains the telomeric DNA at eukaryotic chromosome ends. p65 is important for the ordered assembly of telomerase RNA (TER) with telomerase reverse transcriptase. Unexpectedly, Schizosaccharomyces pombe Pof8 was recently identified as a LARP7 protein and a core component of fission yeast telomerase essential for biogenesis. LARP7 proteins have a conserved N-terminal La motif and RRM1 (La module) and C-terminal RRM2 with specific RNA substrate recognition attributed to RRM2, first structurally characterized in p65 as an atypical RRM named xRRM. Here we present the X-ray crystal structure and NMR studies of S. pombe Pof8 RRM2. Sequence and structure comparison of Pof8 RRM2 to p65 and human Larp7 xRRMs reveals conserved features for RNA binding with the main variability in the length of the non-canonical helix α3. This study shows that Pof8 has conserved xRRM features, providing insight into TER recognition and the defining characteristics of the xRRM.